Calcifying odontogenic cyst associated with an antral pseudocyst: treatment of an uncommon case report and update of main findings - França,Glória Maria de (2021)
Abstract A calcifying odontogenic cyst may be associated with odontogenic tumors, particularly odontomas. However, the association between calcifying odontogenic cysts and odontogenic cysts is rare. This study aims to report the first case of a calcifying odontogenic cyst associated with an antral pseudocyst. A male patient presented a tumor lesion in his right maxillary alveolar ridge with 6 months of evolution and painful symptoms . An excisional biopsy was performed, and a histopathological diagnosis of calcifying odontogenic cyst associated with an antral pseudocyst was issued. The treatment of choice was lesion enucleation and curettage. The patient has been under follow-up for about 3 years without lesion recurrence, which is typical indolent calcifying odontogenic cyst behavior.